Uma História do tempo presente vista do Sul: editorial - Arend, Silvia Maria Fávero; Cunha, Maria Teresa Santos; Lohn, Reinaldo Lindolfo (Revista Tempo e Argumento, 2021)
Volume 13, Número 34, Ano 2021